Review of Jenkins of Mexico. How a Southern Farm Boy Became a Mexican Magnate, by Andrew Paxman - Pansters, Wil (European Review of Latin American and Caribbean Studies, 2018)
Jenkins of Mexico. How a Southern Farm Boy Became a Mexican Magnate, by Andrew Paxman, Oxford University Press, 2017.